2011
DOI: 10.1261/rna.2006511
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and cytoplasmic localization of neural stem cell microRNAs

Abstract: Although generally regarded as functional in the cytoplasm, a number of microRNAs (miRNAs) have been found in the nucleus, possibly with a role in gene regulation. Here we report that, in fact, a substantial fraction of all human miRNAs are present in the nucleus of neural stem cells. Further, subsets of these miRNAs display consistently higher standardized rank in the nucleus than in the cytoplasm of these cells, as identified with an RT-qPCR technology and confirmed by microarray analysis. Likewise, other mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 50 publications
3
93
2
8
Order By: Relevance
“…The nuclear/cytoplasmic ratio of miRNAs is not very consistent among different reports, which may be due to the different cell lines or tissues used for the examinations. For instance, Jeffries et al (2011) used neural stem cells, while Liao et al (2010) used human nasopharyngeal carcinoma cells to investigate the nucleus-enriched miRNAs, but their top nucleus-localized miRNAs lists have little overlap. These observations also reflect the cell-or tissue-specific preferential expression of miRNAs.…”
Section: Cellular Mirnas Targeting Tata-box Motif Up-regulate the Promentioning
confidence: 99%
“…The nuclear/cytoplasmic ratio of miRNAs is not very consistent among different reports, which may be due to the different cell lines or tissues used for the examinations. For instance, Jeffries et al (2011) used neural stem cells, while Liao et al (2010) used human nasopharyngeal carcinoma cells to investigate the nucleus-enriched miRNAs, but their top nucleus-localized miRNAs lists have little overlap. These observations also reflect the cell-or tissue-specific preferential expression of miRNAs.…”
Section: Cellular Mirnas Targeting Tata-box Motif Up-regulate the Promentioning
confidence: 99%
“…The components of miRISC containing miRNAs, Ago and GW182 family proteins are localized in the cytoplasm, but several instances of evidence indicating their nuclear 1 localization were reported recently (Meister et al 2004;Hwang et al 2007;Till et al 2007;Rüdel et al 2008;Politz et al 2009;Liao et al 2010;Taft et al 2010;Yoo et al 2010;Jeffries et al 2011). In addition, several reports demonstrated that miRISC components are functional in the nucleus as well.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to this canonical model, miRNAs only exert their post-transcriptional regulatory roles in the cytoplasmic compartment. However, evidence has accumulated demonstrating that certain mature miRNAs can re-enter the nucleus, and, in some cases, are even more abundant in the nucleus than in the cytoplasm (Meister et al, 2004;Politz et al, 2006;Hwang et al, 2007;Foldes-Papp et al, 2009;Liao et al, 2010;Jeffries et al, 2011).…”
Section: Presence Of Mirnas In the Nucleusmentioning
confidence: 99%
“…Their results indicated that miR-206 was not only distributed throughout the cytoplasm but also concentrated in the nucleus (Politz et al, 2006). Using high-throughput profi ling technology, such as microarrays and deep sequencing, researchers compared the levels of mature miRNAs in both cytoplasmic and nuclear fractions and reported that many miRNAs were located in both the cytoplasm and the nucleus (Liao et al, 2010;Jeffries et al, 2011). These results indicated that the presence of mature miRNAs in the nucleus is a general phenomenon in mammalian cells.…”
Section: Presence Of Mirnas In the Nucleusmentioning
confidence: 99%
See 1 more Smart Citation